Health Communication for Professional Nurses - Chaichana, Jiranat (Journal of Nursing, Siam University, 2024)
Health communication is a crucial aspect of nursing practice, playing a vital role in patient care, education, and support, as well as in understanding the needs of service recipients. This academic article discusses the importance of health communication for nurses, emphasizing the significance of establishing effective interactions between healthcare providers, patients, and their families. Essential skills for high-quality health communication, such as active listening, empathetic understanding, culturally sensitive communication, and clarity in conveying information, are highlighted. Additionally, this article addresses the challenges posed by complex health information, such as cultural and linguistic differences. It also introduces various methods and tools that enhance nurses' communication skills, such as health communication models, the use of technology to aid communication, and strategies for fostering collaboration among interprofessional teams. The article underscores the positive outcomes of effective health communication, including improved patient care results, increased patient satisfaction with nursing services, and overall quality of care. This article provides evidence-based practices, guidelines, and recommendations on effective health communication to support professional nurses in enhancing their communication skills. Ultimately, this contributes to improved healthcare service quality and fosters a positive experience between nurses and service recipients.